2021
DOI: 10.1088/1742-6596/1845/1/012037
|View full text |Cite
|
Sign up to set email alerts
|

Static Analysis of Railway Axle using Finite Element Method and Monitoring of Railway Bearing Based on Vibration Analysis

Abstract: Railway axle and railway bearing are critical railway components. It is needed a method to analyse them. In this work, static and dynamic analysis are presented. Static analysis is presented by analyzing the design of railway axle through finite element analysis (FEA). Dynamic analysis is presented by analysing the outer race fault of the railway axle bearing based on vibration analyses. Initially, a laboratory-scale of wheel-set test-rig was designed using 3D computer design, then, the design was analysed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…As long as the bearing vibrates and reaches a certain frequency, the noise will be generated [100]. The rolling bearing inspection of trains is mainly divided into static monitoring and dynamic monitoring [101]. Static monitoring needs to be carried out when the train is stopped.…”
Section: Fault Diagnosis Of Wayside Acoustic Features On Train Bearingsmentioning
confidence: 99%
See 1 more Smart Citation
“…As long as the bearing vibrates and reaches a certain frequency, the noise will be generated [100]. The rolling bearing inspection of trains is mainly divided into static monitoring and dynamic monitoring [101]. Static monitoring needs to be carried out when the train is stopped.…”
Section: Fault Diagnosis Of Wayside Acoustic Features On Train Bearingsmentioning
confidence: 99%
“…Static monitoring needs to be carried out when the train is stopped. It would take up the scheduling time of the train, while the detection speed is slow and the labor intensity of the maintenance workers is exceedingly high [101]. The dynamic monitoring, however, can complete the state monitoring of the bearing during the running of the train and provide real-time feedback of the bearing status to realize online monitoring [102].…”
Section: Fault Diagnosis Of Wayside Acoustic Features On Train Bearingsmentioning
confidence: 99%
“…Johnson et al (2022) used FEM in the structural analysis of a lightweight composite railway axle, while Son et al (2014) used FEM to simulate the static strength of different axle sizes to determine the appropriate design for the axle's inner diameter. Asngali et al (2021) employed FEM for static and dynamic analysis in the design of a railway axle and found that the stress and deformation were within the desired standard requirements. Wu (2009) conducted a comparative study of different methods for analyzing the strength of high-speed train axles, and Xiao et al (2014) conducted FEM analysis on a non-power axle of a CRH2 EMU, considering the effect of interference fit between the wheel-axle and disk-shaft on static strength.…”
Section: Introductionmentioning
confidence: 99%
“…(2014) used FEM to simulate the static strength of different axle sizes to determine the appropriate design for the axle's inner diameter. Asngali et al. (2021) employed FEM for static and dynamic analysis in the design of a railway axle and found that the stress and deformation were within the desired standard requirements.…”
Section: Introductionmentioning
confidence: 99%
“…The train ensures the safety, comfort, and safety of passengers [2]. Railroad axles are one of the key components of train [3]. They should retain the weight of the body and transfer it to the wheels [4].…”
Section: Introductionmentioning
confidence: 99%